'Samae Spirit' Assist toward 'Ubuntu Spirit' Model for Rural Adult Christian Education in Zambia. Issue 1 (1st January 2022) - Kaunda, Chammah J.; Kim, Sang-man
Abstract: This article argues that in the ongoing effort to promote ubuntu spirit as an instrument for decolonization, the church in Zambia can learn lessons from how Rev Pai Min-soo deployed the indigenous model of samae spirit to construct adult Christian education for Korean rural development. The samae spirit is utilized to underline the necessity for the affirmation of the ubuntu spirit for the critical consciousness of the rural dwellers in Zambia. It stresses that while non-African models cannot substitute indigenous decolonial models, they can assist in understanding how postcolonial African contexts can leverage indigenous knowledge systems for social transformation.